Threadfin Porgy (Evynnis Cardinalis) Haplotype Pattern and Genetic Structure in Beibu Gulf, South China Sea - Xu, Lei; Wang, Xuehui; Wang, Lianggen; Ning, Jiajia; Li, Yafang; Huang, Delian; Liu, Shuangshuang; Du, Feiyan (Frontiers in Environmental Science, 2021)
Threadfin porgy (Evynnis cardinalis) is an important commercial fishing target of bottom trawl fisheries in the northern South China Sea. It is mainly threatened by overexploitation and listed as endangered in the IUCN Red List. To investigate E. cardinalis population demographic history and genetic structure, fragments of the mitochondrial cytochrome c oxidase subunit I gene were sequenced for 162 individuals collected from Beibu Gulf, South China Sea. In total, 44 different haplotypes were identified, and the dominant widespread haplotype was found in all 11 sampling sites. Across the dataset, nucleotide diversity was low but haplotype diversity was high. Low pairwise comparisons of ΦST and high gene flow between all sampling sites revealed a genetically homogeneous population structure in Beibu Gulf, which indicated a single panmictic stock of E. cardinalis in this area. The star-like haplotype network, unimodal mismatch distribution, and significantly negative Tajima’s D and Fu’s Fs values indicated recent population demographic expansion of E. cardinalis. The mismatch distribution and Bayesian skyline plot results indicated that E. cardinalis from Beibu Gulf experienced colonization and demographic expansion during the late Pleistocene due to sea level fluctuations.